2018
DOI: 10.21772/ripo.v37n1a03
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Exposure to Workplace Bullying on Turnover Intention and The Mediating Role of Job Satisfaction, Work Engagement, and Burnout

Abstract: Statement of the Problem: One of the great challenges for organizations today is the retention of valuable human resources because this is essential to them for being globally competitive and one of the factors that can exacerbate turnover intention is the exposure to workplace bullying. Purpose: The purpose of the present investigation was to examine the effect of exposure to psychological harassment on the intention to give up employment and how job satisfaction, work engagement and burnout mediate the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 90 publications
3
13
0
Order By: Relevance
“…The analysis results showed that workplace bullying has a positive and significant effect on turnover intention, and these results are in line with the other studies (Bohle et al, 2017; Coetzee & Dyk, 2018; Laschinger & Fida, 2014; Rosario‐Hernández et al, 2018). This research suggested that workplace ostracism has a positive and significant effect on turnover intention just like some other studies (Lyu et al, 2019; Mahfooz et al, 2017; Miner et al, 2019; Turkoglu & Dalgic, 2019).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The analysis results showed that workplace bullying has a positive and significant effect on turnover intention, and these results are in line with the other studies (Bohle et al, 2017; Coetzee & Dyk, 2018; Laschinger & Fida, 2014; Rosario‐Hernández et al, 2018). This research suggested that workplace ostracism has a positive and significant effect on turnover intention just like some other studies (Lyu et al, 2019; Mahfooz et al, 2017; Miner et al, 2019; Turkoglu & Dalgic, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Some other researches have shown that workplace bullying is also a predictor of turnover intention, and the effect of workplace bullying on turnover intention is positive (Ahmad & Kaleem, 2020; Bohle et al, 2017; Coetzee & Dyk, 2018; Hsieh et al, 2019; Laschinger & Fida, 2014; Rosario‐Hernández et al, 2018). Many academicians suggested that workplace ostracism has a positive effect on turnover intention (Lyu et al, 2019; Mahfooz et al, 2017; Miner et al, 2019; Turkoglu & Dalgic, 2019).…”
Section: Conceptual Model and Hypotheses Developmentmentioning
confidence: 99%
“…A total of 4,100 protocols from five different research conducted by the authors ( Rosario-Hernández et al, 2013 , 2015 , 2018a , b , 2019 , 2020 ) in Puerto Rico and each selected through a non-probabilistic sample, and distributed into this five large groups: sample 1 ( n = 518, 12.6%), sample 2 ( n = 1046, 25.5%), sample 3 ( n = 1107, 27.0%), sample 4 ( n = 626, 15.3%), and sample 5 ( n = 803, 19.6%). The distributional differences in the five samples in sex (χ 2 [5] = 13.29, p = 0.02, Cramer’s V = 0.053), level of education (Kruskall–Wallis’ H [5] = 52.56, p < 0.01, χ 2 = 0.01) and age (Kruskall–Wallis’ H [5] = 74.97, p < 0.01, χ 2 = 0.01), although they were statistically significant, the effect size was trivial, that is, η 2 = 0.02.…”
Section: Methodsmentioning
confidence: 99%
“…The WRRS was translated into Spanish and has been used in several studies in occupational health psychology in Puerto Rico ( Rosario-Hernández et al, 2013 , 2015 , 2018a , b , 2019 , 2020 ); however, psychometric properties of the WRRS have not been examined. Therefore, the purpose of the current study was to examine the internal structure, psychometric properties, and measurement invariance of the WRRS – Spanish version across gender and age.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of bullies is also a potential moderator variable that determines employee decisions for intention to stay (Bahjat, Aljawazneh, Moh, Smadi, & Ziad, 2017). Both of these studies were later strengthened by (Rosario, Millán, Ramos, Cruz, Vélez, Torres, & Rodríguez, 2018) where the interrelated effects created by bully behavior can cause decreased job satisfaction, work engagement and stress.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%